2023
DOI: 10.3389/fpls.2023.1138563
|View full text |Cite
|
Sign up to set email alerts
|

The combined formulation of brassinolide and pyraclostrobin increases biomass and seed yield by improving photosynthetic capacity in Arabidopsis thaliana

Abstract: In the context of global food crisis, applying the phytohormone-brassinosteroids (BRs) in combination with the fungicide-pyraclostrobin (Pyr) was beneficial for plant quality and productivity in several field trials. However, in addition to the benefits of disease control due to the innate fungicidal activity of Pyr, it remains to be understood whether the coapplication of BL+ Pyr exerts additional growth-promoting effects. For this purpose, the effects of BL treatment, Pyr treatment, and BL+ Pyr treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…Research has found that some fungicides could promote plant growth. 53 Therefore, to explore whether our newly synthesized compounds could promote plant growth or not, compound Ip with promising fungicidal activity was selected for the subsequent plant growth-promoting activity experiments. The results showed that Ip showed higher activity than pydiflumetofen in promoting the growth of wheat seedlings at concentrations of 2−20 μM (Table S4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that some fungicides could promote plant growth. 53 Therefore, to explore whether our newly synthesized compounds could promote plant growth or not, compound Ip with promising fungicidal activity was selected for the subsequent plant growth-promoting activity experiments. The results showed that Ip showed higher activity than pydiflumetofen in promoting the growth of wheat seedlings at concentrations of 2−20 μM (Table S4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Research has found that some fungicides could promote plant growth . Therefore, to explore whether our newly synthesized compounds could promote plant growth or not, compound Ip with promising fungicidal activity was selected for the subsequent plant growth-promoting activity experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration range of BL and Pyr was chosen based on our previous study with A. thaliana, where exogenous application of Pyr exceeding 3 μM and BL exceeding 1 μM both caused phytotoxicity, while exogenous application of Pyr below 0.03 μM and BL below 0.1 μM both did not significantly alter plant phenotype …”
Section: Methodsmentioning
confidence: 99%
“…The concentration range of BL and Pyr was chosen based on our previous study with A. thaliana, where exogenous application of Pyr exceeding 3 μM and BL exceeding 1 μM both caused phytotoxicity, while exogenous application of Pyr below 0.03 μM and BL below 0.1 μM both did not significantly alter plant phenotype. 29 For the subsequent experiments to comprehensively study the effect of BL + Pyr on disease resistance, the uniform seedlings were picked out and randomly divided into 4 groups. Those 4 groups were foliar sprayed with 1‰ DMSO, BL (1 μM), Pyr (3 μM), and a mixture of BL (1 μM) and Pyr (3 μM), respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation